Enacting refusals: Mestiza women's anti-mining activism in Andean Ecuador. Issue 3 (2nd September 2017) - Velásquez, Teresa A
ABSTRACT: Subaltern mestiza women are protagonists in anti-mining activism in Ecuador, but few works consider the racial and gendered dimensions of their political practices. Drawing upon activist research methods, this paper examines the role of ethnographic 'refusals' in the collective practices of campesina women. I argue that refusals, predicated upon speaking, are critical to forging a collective identity as a 'defensora': a woman who defends land and watersheds from state and multinational mining projects. This paper considers how women tack back and forth between 'speaking' and 'refusals' to show the complex dynamics of speech and silence that women use to challenge race, space, and gender relations in Cuenca, Ecuador in promising but potentially limited ways. Their strategic use of productive negations challenge sexism within the anti-mining movement and representations of rural women as chola cuencanas, a racialized folkloric figure in the regional imaginary, as well as certain aspects of activist research. Yet, struggling from spaces of mestizaje means that women may not fully able to challenge the racialized dynamics that affect their position in local resource conflicts.